Coping the Academic Stress: The Way the Students Dealing with Stress - Aina, Q; Hermilia Wijayati, P (KnE Social Sciences, 2019)
In the educational setting, academic stress has been obviously seen as one of the vital topic. The broad of academic stress sources and the variety of students’ coping strategies emerge as the essential factors in this field. Hence, this study is intended to ascertain the students’ causes and coping strategies in concerning the academic stress. A survey method was called for collecting and analyzing the data. Further, two questionnaires were entrusted in grasping the academic stress causes and coping strategies namely perception of academic stress scale (PAS) and brief cope (pldts). The data interpretation affirms that the substantial source of academic stress is the students’ worries about their examinations in which 60% students admitting this subscale. Simultaneously, the prevalent coping strategies work with the subjects are finding the comfort feeling in spiritual beliefs by praying or meditating (52.6%) whilst accepting the reality and trying to live with it (52.6%). Stress has been one of the most important topics in academic issues. There are many sources of academic stress and the way of students cope the stress may differ. Therefore, this study is aimed to find out the sources of students’ academic stress and what they are doing when they are in such condition. A survey method was chosen in collecting and analyzing the data. There are two questionnaires that had been given to the subjects of the study for these purposes. The first questionnaire is Perception of Academic Stress Scale (PAS) which used to analyze the causes of academic stress and the second questionnaire is brief cope (ptlds) which used to analyze the way the students cope their stress. The results showed that the main sources of academic stress is the students’ worries about their examinations in which 60% students are agree with this subscale. Moreover, in dealing with the academic stress, more than half of the students (52.6%) are frequently used to find the comfort feeling in spiritual beliefs by praying or meditating while accepting the reality and try to live with it (52.6%). In contrast, there only a very few of the students (5.3%) are rarely using drugs and alcohol to make themselves feel better. Keywords: coping academic stress, academic stress, coping strategies, sources of academic stress